2019
DOI: 10.1103/physrevlett.123.133901
|View full text |Cite
|
Sign up to set email alerts
|

Semidiscrete Quantum Droplets and Vortices

Abstract: a These two authors contributed equally to this paper.We consider a binary bosonic condensate with weak mean-field (MF) residual repulsion, loaded in an array of nearly one-dimensional traps coupled by transverse hopping. With the MF force balanced by the effectively one-dimensional attraction, induced in each trap by the Lee-Hung-Yang correction (produced by quantum fluctuations around the MF state), stable onsite-centered and intersite-centered semi-discrete quantum droplets (QDs) emerge in the array, as fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 77 publications
0
42
0
Order By: Relevance
“…Such tightly localized semidiscrete modes were not reported in the previously studied semidiscrete system. [ 58 ] In fully discrete 2D models, the possibility that the smallest vortex soliton includes four sites was theoretically predicted [ 10 ] and experimentally demonstrated. [ 12,13 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such tightly localized semidiscrete modes were not reported in the previously studied semidiscrete system. [ 58 ] In fully discrete 2D models, the possibility that the smallest vortex soliton includes four sites was theoretically predicted [ 10 ] and experimentally demonstrated. [ 12,13 ]…”
Section: Resultsmentioning
confidence: 99%
“…This definition is adopted from the previous study, [ 58 ] where ε=1 implied that solitons were effectively isotropic modes, whereas ε>1 and ε<1 indicated that their shape was anisotropic, namely, elongated in the continuous or discrete direction, respectively. Figure 6c displays ε as a function of P for the compact vortex solitons with (N,Ncore)=(4,0) and (N,Ncore)=(5,1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last few years, self-bound quantum droplets (QDs) in ultracold atoms have attracted increasing attention from both experimental and theoretical research [1][2][3][4][5][6][7][8][9][10][11][12][13]. In the pioneering theoretical work [14], the threedimensional (3D) QDs were predicted as stable solitonlike states in binary Bose-Einstein condensates (BECs) due to the balance between the attractive mean-field interaction (the inter-component attraction being slightly stronger than the intra-component repulsion) and the repulsive Lee-Huang-Yang (LHY) correction originating from quantum fluctuation [15], on the basis of a system of coupled mean-field Gross-Pitaevskii equations.…”
Section: Introductionmentioning
confidence: 99%